A theory and outcome evaluation of the Allan Gray Orbis Foundation's (AGOF's) scholarship programme - Onyango, Kevin Rombo (Accounting and Accountability in Africa, 2026)
This report presents the results of the formative (theory and outcome) evaluation of the Allan Gray Orbus Foundation (AGOF) scholarship programme. The programme offers scholarships to academically excellent grade 6 learners of 11 to 12 years of age, who demonstrate financial need and attain a minimum score of 70% in English and Mathematics and are from poor family backgrounds to attend secondary school. The programme provides financial support, coaching, and extracurricular activities (a development camp, breakthrough sessions, jamborees and an online curriculum) to help needy students access high-quality secondary education and develop an entrepreneurial mindset. The financial support covers tuition, boarding, allowances, uniforms, stationery and extracurricular expenses. Scholars receive academic support through tutoring and remedial lessons, particularly in mathematics, science, and English. Further, the students attend extracurricular activities that comprise of camps, breakthrough sessions and jamborees, gaining networking and entrepreneurial exposure. Graduates meeting this academic criterion can apply for the fellowship programme and contribute to society and the economy.